Molecular detection, characterisation and serological survey of chicken astrovirus from broiler flocks in Malaysia - Abdullahi Raji, Abdullahi; Ideris, Aini; Bejo, Mohd Hair; Omar, Abdul Rahman (Universiti Putra Malaysia, 2022)
Astroviruses have been associated with enteric and extra-intestinal disorders in many animal species, including chickens. Here, we describe the detection and characterisation of chicken astrovirus (CAstV) in broilers and its seroprevalence in broiler breeder flocks. Based on PCR protocol, viral confirmation was carried out on clinical tissue samples from broiler chickens suffering from uneven growth and poor performance. The tissues were molecularly detected for CAstV with differential diagnostic testing against the Newcastle disease virus, infectious bronchitis virus, avian nephritis virus, avian rotavirus, fowl adenovirus and avian reovirus. Polymerase gene-based phylogenetic analyses of the twenty samples detected positive for CAstV indicate they belong to Group I and are related to strains from the US, UK, India and Poland. From these 20 samples, CastV could be isolated from 3 samples upon inoculation in 5-day-old specific-pathogen-free (SPF) embryonated chicken eggs (ECE); virus-infected embryos showed dwarfing, haemorrhages, oedema and gelatinous lesions at harvest. The enzyme-linked immunosorbent assay (ELISA) results revealed a high prevalence of antibodies against CAstV amongst the broiler breeder flocks tested. It is the first study that describes the detection and prevalence of CAstV in broiler chickens and broiler breeder flocks in Malaysia.